Valuation of reverse mortgages : an empirical investigation using portuguese data - Gonçalves, Ana Cristina Santos (2018)
Dissertation presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Risk Analysis and Management